2008
DOI: 10.1002/jcp.21596
|View full text |Cite|
|
Sign up to set email alerts
|

Sustained NF‐κB activation produces a short‐term cell proliferation block in conjunction with repressing effectors of cell cycle progression controlled by E2F or FoxM1

Abstract: NF-κB transcription factors induce a host of genes involved in pro-inflammatory/stress-like responses; but the collateral effects and consequences of sustained NF-κB activation on other cellular gene expression programming remain less well understood. Here enforced expression of a constitutively active IKKβ T-loop mutant (IKKβca) drove murine fibroblasts into transient growth arrest that subsided within 2-3 weeks of continuous culture. Proliferation arrest was associated with a G1/S phase block in immortalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 98 publications
2
43
0
3
Order By: Relevance
“…However, up to now, the precise molecular regulation of FoxM1 and NF-κB and their cross-talks for elucidating the role of FoxM1 in oncogenesis is not clear, but Penzo et al [28] found that inhibition of NF-κB by IκBβα super repressor in the mouse embryonic fibroblasts abrogated both the IκKβ-mediated induction of direct NF-κB targets and the repression effect on the FoxM1 targets. Moreover, Gieling et al [20] reported that NF-κB subunit c-Rel is required for appropriate timing of the induction of FoxM1 and is a transcriptional regulator of FoxM1 during liver regeneration.…”
Section: Discussionmentioning
confidence: 97%
“…However, up to now, the precise molecular regulation of FoxM1 and NF-κB and their cross-talks for elucidating the role of FoxM1 in oncogenesis is not clear, but Penzo et al [28] found that inhibition of NF-κB by IκBβα super repressor in the mouse embryonic fibroblasts abrogated both the IκKβ-mediated induction of direct NF-κB targets and the repression effect on the FoxM1 targets. Moreover, Gieling et al [20] reported that NF-κB subunit c-Rel is required for appropriate timing of the induction of FoxM1 and is a transcriptional regulator of FoxM1 during liver regeneration.…”
Section: Discussionmentioning
confidence: 97%
“…This protein binds preferentially to retinoblastoma protein pRB in a cell-cycle dependent manner. It can mediate both cell proliferation and p53-dependent/independent apoptosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…As a potential oncogene, FOXM1 is activated by oncogenic Ras-MAPK, Sonic Hedgehog, NF-kB and EGFR pathways, and negatively regulated by tumor suppressor p53 [13][14][15][16][17]. When FOXM1 becomes overactivated in cancers, it abberently induce cycle progression by transcriptionally activate genes that are involved in cell cycle such as Cyclin B, Cdc25b phosphatase, Plk1, Skp2 and Cks1 [18].…”
Section: Discussionmentioning
confidence: 99%